Modal Sosial dalam Strategi Akses Pasar Komoditas Jeruk Siam (Studi Kasus Komoditas Jeruk Siam desa Sambimulyo Banyuwangi) - Syahid, Mar (MOMENTUM : Jurnal Sosial dan Keagamaan, 2018)
Banyuwangi is an area that is active in producing Siamese citrus commodities. One of the areas or villages that produce agricultural products of Siamese Citrus is Sambimulyo Banyuwangi village. The process of transferring the commodity of citrus is called the market access strategy, because farmers are producers who need two distribution intermediaries played by middlemen and retailers. The theoretical framework of this research is based on social capital, Woolcock's theory, where it defines social capital as information, trust, and reciprocal norms contained in a social network. Methods in qualitative research, with a phenomenological approach. While the validity test of the data in this study uses a test of credibility, transferability, dependability and commitment. The results of this study explain that the market access strategy for Siamese commodities includes distribution by region which is divided into 2 regions. First, the distribution of siam citrus commodities in one region, which means thefulfillment of siam orange for its own regional market. Second, the distribution of siwam citrus commodities to other regions or regions, which means sending commodities from Siamese oranges to other regional markets that make requests